Electron microscopic study of Esophageal Epithelium in Non-erosive Reflux disease - Myint, Yi Yi; Tun, Ye; Mohammad Amjad, Nasser; Mat Hassan, Mohd. Zailani; Abdul Rashid, Nor Linda (2011)
Introduction: Non-erosive reflux disease (NERD) is the most common phenotype of gastro esophageal reflux disease (GERD). Dilated intercellular spaces (DIS) in prickle cell layers are considered as early signs of acid damage to the esophageal epithelium. Objectives: The objective of this study was to explore DIS in both superficial and prickle cell layer of the esophageal epithelium of NERD patients and normal controls by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Material and methods: The study group included 5 normal controls and 8 NERD patients with reflux symptoms, normal mucosa on endoscopy and positive 24-hour pH monitoring. Specimens were taken 5 cm above the Z line during gastroduodenoscopy and then routinely processed for both SEM & TEM studies. The nature of intercellular spaces between superficial cells and prickle cell layers were viewed by TEM and SEM respectively. Results: We found out that cellular attachments in the superficial cells differ significantly between the normal controls and patients with NERD (p value 0.007). Morphometric analysis of TEM microphotographs showed that the mean intercellular space diameter values of NERD patients were significantly ( two times) higher than that in normal controls (p<0.001). Conclusions: We can conclude that SEM study on DIS in esophageal surface cells is not a useful diagnostic test for differentiating between normal and NERD patients but TEM study in prickle cell layer is a promising diagnostic finding of early damage of esophageal epithelium.